Intelligent Drip Irrigation System Using Linear Programming and Interpolation Methodology - Wavhal, Dnyaneshwar Natha; Giri, Manish (International Journal of Computer (IJC), 2014)
In this paper, the Design of Intelligent Drip Irrigation system for the Automation of Drip irrigation is presented. Generally the Drip irrigation was named in Israel in 1959. Drip Irrigation is today’s need because water is nature’s gift to the mankind and it is not unlimited and free forever. World’s water resources are fastly vanishing. The one and only one solution to this problem is Intelligent Drip Irrigation system. In the conventional drip irrigation system, the farmer has to keep watch on irrigation timetable, which is different for different crops. In Intelligent Drip Irrigation using Linear Programming irrigation will take place only when there will be intense requirement of water. Irrigation system uses valves to turn irrigation ON and OFF. These valves may be easily automated by using controllers and solenoids. The developed irrigation method removes the need for workmanship for flooding irrigation as well as drip irrigation along with that it allows the farmer to apply the right amount of water at the right time, regardless of the availability of the labour to turn valves or motor ON & OFF. In this presented Intelligent Irrigation system I have used linear programming concept and Interpolation Method. Linear Programming helps us to distribute available water to the number of crops in order to get maximum profit with minimum cost. Also linear Programming helps us to do proper management of available water. Interpolation Method is used to map the physical parameters readings in the farm where taking manual readings is not possible. Finally both the methodology helps us to increase productivity of the crops and ultimately profit.